Do co-opted boards increase insider profitability? - Rahman, Dewan; Malik, Ihtisham; Ali, Searat; Iqbal, Jamshed (Elsevier, 2021)
Using a sample of U.S. firms over the period 1996–2014, this paper examines whether insider trading profitability increases with high board co-option. Indeed, we find that firms with a higher level of co-opted directors exhibit higher insider trading profitability, largely due to a lower level of managerial ability and analyst coverage. Co-opted boards are also unlikely to implement self-imposed insider trading restrictions, exacerbating this relationship. This positive association is mitigated by a higher level of external monitoring by institutional investors and if the CEO receives more performance-based incentives. Overall, co-opted directors demonstrate aligned interests with CEOs and corporate insiders rather than performing their role as monitors. As a result, a more co-opted board is positively associated with exploitative behaviour of insiders.
Keywords: Co-opted boards; Market-adjusted buy-and-hold abnormal returns; insider trading; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|